Detection of Ammonia in Liquids Using Millimeter Wave Spectroscopy - Hilmi Ozturk; Hakki Nazli; Korkut Yegin; Mehmet Sezgin (International Journal of Photoenergy)
Detection of ammonia plays a vital role for counter-bioterrorism applications. Using millimeter wave absorption measurements, ammonia dissolved in water solution is analyzed and compared to water-only solution. The inversion of ammonia molecule results in split rotational spectral lines and transitions of these lines can be detected. Two-port measurements were carried out with vector network analyzer and measurements revealed that ammonia presence can be identified, especially between 30–35 GHz.